2016
DOI: 10.1002/cbin.10612
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic acid induces autophagic death in human gastric cancer cells in vitro and in vivo

Abstract: Oleanolic acid (OA), a plant-derived pentacyclic terpenoid, is known to have hepatoprotective effects. In this study, we found that OA induced autophagic cell death in multiple human gastric cancer cell lines. Moreover, OA-induced autophagy was shown for the first time in human gastric cancer cells, evidenced by the formation of GFP-RFP-LC3 puncta and autophagosomes. OA suppressed phospho-mTOR through inhibition of the PI3 K/AKT and ERK/p38 MAPK signalling pathways and through activation of the AMPK signalling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Increasing research reported that AMPK plays an important role in inflammation, and metformin can serve as a potential drug to treat inflammation‐related disorders. Adenosine 5′‐monophosphate‐activated protein kinase is activated by natural products, such as ginsenoside (Yao et al, ), oleanolic acid (Nie et al, ) and ursolic acid (Meng et al, ), all of which suppress the release of inflammatory cytokines in LPS‐induced ALI. It has been demonstrated that mogroside V and its aglycone (mogrol) are both potent AMPK activators (Chen et al, ; Harada et al, ; Luo et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Increasing research reported that AMPK plays an important role in inflammation, and metformin can serve as a potential drug to treat inflammation‐related disorders. Adenosine 5′‐monophosphate‐activated protein kinase is activated by natural products, such as ginsenoside (Yao et al, ), oleanolic acid (Nie et al, ) and ursolic acid (Meng et al, ), all of which suppress the release of inflammatory cytokines in LPS‐induced ALI. It has been demonstrated that mogroside V and its aglycone (mogrol) are both potent AMPK activators (Chen et al, ; Harada et al, ; Luo et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, over-expression of Akt also reversed the effects of oleanolic acid [60]. Importantly, oleanolic acid is also an inhibitor of extracellular signal–regulated kinase/c-Jun N-terminal kinase/mitogen-activated protein kinase (ERK/JNK/p38 MAPK) signaling pathway mediated by the activation of the 5′ adenosine monophosphate-activated protein kinase (AMPK) signaling pathway that consequently activates downstream signaling leading to the mTOR inhibition and activation of autophagy [55,68,73]. A significant decrease in p-p38α/p38α ratio and in the levels of p-JNK1 and pERK1/2 together with the increased phosphorylation of AMPK were reported in oleanolic acid-treated cancer cells [74].…”
Section: Oleanolic Acid As Anticancer Agentmentioning
confidence: 99%
“…Oleanolic acid derivative, SZC015, activated intrinsic apoptosis, as observed by the up-regulation of caspase-3 and caspase-9, poly (ADP-ribose) polymerase (PARP) cleavage, release of cytochrome c, as well as increase in Bax/Bcl-2 expression ratio [55,87]. Moreover, oleanolic acid and its derivatives also caused autophagy, i.e., formation of autophagic vacuoles, elevated microtubule-associated protein 1 light chain 3α (MAP1LC3A), increased LC3II/LC3I ratio and upregulated the expression of Atg5 and beclin1 in hepatic [50], breast [55] and gastric cancer cells [73,87]. Interestingly, oleanolic acid-triggered autophagy was ROS-dependent as shown by elevated cellular ROS levels, and the effect was abolished if ROS levels were reduced [50,62].…”
Section: Oleanolic Acid As Anticancer Agentmentioning
confidence: 99%
“…OA-induced autophagy was shown for the first time in human gastric cancer cells, evidenced by the formation of GFP-RFP-LC3 puncta and autophagosomes. OA suppressed phospho-mTOR through inhibition of the PI3 K/AKT and ERK/p38 MAPK signalling pathways and through activation of the AMPK signalling pathway [21]. Hepatocellular carcinoma (HCC) is an aggressive form of cancer, with high rates of morbidity and mortality, a poor prognosis and limited therapeutic options.…”
Section: Discussionmentioning
confidence: 99%